Konsepsi Guru Matematika SMA tentang Berpikir Kreatif - Wicaksono, Arief Budi; Khabibah, Siti; Masriyah, Masriyah (Edumatica : Jurnal Pendidikan Matematika, 2022)
This study aims to describe the high school mathematics teachers' conceptions of creative thinking. The research approach used is descriptive qualitative. The subject in this study was a high school mathematics teacher in Yogyakarta. This study uses the results of an open questionnaire as the main data and interviews as supporting data. The results of the study show that the mathematics teachers' conceptions of creative thinking are limited to ways of thinking/solving a problem by using new steps or ideas so as to find/produce something new/different from usual. Creative mathematics teachers are described as being able to come up with new ideas, being able to make new innovations in learning. The teacher plays an active role in guiding students to be able to think creatively by giving questions or assignments that trigger mathematics in the form of descriptions (open questions) so that students can explore their abilities to trigger their creative thinking. The teacher assesses the ability to think creatively by giving open questions/trigger assignments and then analyzing the steps/results of the work to find new steps/ideas in the process.